MARKETING STRATEGIES DEVELOPMENT APPROACHES FOR MANAGING PATENT PORTFOLIOS - R. Tokarev (Вестник университета)
In the article an approach for the implementation of innovations is presented, where at the implementation stage a specific approach of use of the results of technological developments and marketing is being developed. The main directions of the strategy at the stage of forming a business idea are shown with the aim of using intellectual property and based on which building the strategy of the whole business in the future is provided. We consider the development of a patent marketing strategy that includes analysis of market needs, consideration of the legal norms of each of the markets, and accounting for business risks. The main stages of development a marketing patent strategy for different types of enterprises are given.